Motivaciones situacionales y transituacionales de uso de redes sociales (2023)
In today's digital age, the use of social networks has become ubiquitous, transforming the way people relate, communicate and share information. This degree project delves into the complex web of motivations that drive the use of social networks, exploring both situational and trans - transactional factors. In this study, it aims to contrast the fundamental reasons that drive young people in the city of Cali to use social networks such as TikTok, Instagram, What sApp and YouTube. Among the most salient findings of this research, specific motivations were identified for each platform.